PEMANFAATAN KITOSAN DARI LIMBAH CANGKANG KERANG BULU(Anadara inflata) SEBAGAI BAHAN PENJERNIH AIR SUNGAING DARI LIMBAH KULIT DURIAN - Rosliana Lubis; Muhammad Usman (Universitas Medan Area, 2014)
The title of this study is the utilization of chitosan from shellfish waste as water purifier. The purpose of the study is to utilize coagulant of shellfish waste in water treatment proes into clear water. The research variabel are the concentration of chitosan 1,3,5,7, and 9 g/l. The particle size of chitosan used in this research is 150 mesh. The time consume 8 hours for purification process. The result showed that 9 g/l chitosan shell waste is effective to water purification process. At a concentration of 9 g/l. Chitosan shellfish waste can produce clean water in complianee with health minister No. 416/MENKES/PER/IX/1990 about water quality treatment.